Realitas Hidup Sosial dalam Cerpen “Ibu Kota” Karya Silvester Petara Hurit (Jurnal Motivasi Pendidikan dan Bahasa, 2025)
This study aims to describe the reality of social life in the short story "Ibu Kota" by Silvester Petara Hurit. By using the theory of literary sociology and descriptive qualitative research methods, the researcher analyzed and obtained the following research results, (1) the city as a space that is oppressive and unfriendly, (2) social inequality and moral decadence (3) the destruction of cultural values ​​and communal life, (4) alienation in urban life, and (5) the symbolism of the city as a misleading hope